Lubiprostone activates non-CFTR-dependent respiratory epithelial chloride secretion in cystic fibrosis mice - MacDonald, Kelvin D. (American Physiological Society, 2008)
Periciliary fluid balance is maintained by the coordination of sodium and chloride channels in the apical membranes of the airways. In the absence of the cystic fibrosis transmembrane regulator (CFTR), chloride secretion is diminished and sodium reabsorption exaggerated. ClC-2, a pH- and voltage-dependent chloride channel, is present on the apical membranes of airway epithelial cells. We hypothesized that ClC-2 agonists would provide a parallel pathway for chloride secretion. Using nasal potential difference (NPD) measurements, we quantified lubiprostone-mediated Cl(−) transport in sedated cystic fibrosis null (gut-corrected), C57Bl/6, and A/J mice during nasal perfusion of lubiprostone (a putative ClC-2 agonist). Baseline, amiloride-inhibited, chloride-free gluconate-substituted Ringer with amiloride and low-chloride Ringer plus lubiprostone (at increasing concentrations of lubiprostone) were perfused, and the NPD was continuously recorded. A clear dose-response relationship was detected in all murine strains. The magnitude of the NPD response to 20 μM lubiprostone was −5.8 ± 2.1 mV (CF, n = 12), −8.1 ± 2.6 mV (C57Bl/6 wild-type, n = 12), and −5.3 ± 1.2 mV (AJ wild-type, n = 8). A cohort of ClC-2 knockout mice did not respond to 20 μM lubiprostone (n = 6, P = 0.27). In C57Bl/6 mice, inhibition of CFTR with topical application of CFTR inhibitor-172 did not abolish the lubiprostone response, thus confirming the response seen is independent of CFTR regulation. RT-PCR confirmed expression of ClC-2 mRNA in murine lung homogenate. The direct application of lubiprostone in the CF murine nasal airway restores nearly normal levels of chloride secretion in nasal epithelia.